Career anchors of young people: the experience of Russian studies (overview) - Polyanskaya, Ekaterina (2020)
The article strives to analyze, systematize and consolidate the findings of empirical research into career orientations of Russian youth through the prism of E. Schein’s anchor conception and on the basis of the various versions of his questionnaire. It was revealed that career orientations in adolescence are characterized by low differentiation, declarative nature, low awareness and contradiction. The article shows that youth career anchors are conditioned by such factors as the year of training, gender, training orientation and type of occupation. Female students are generally inclined towards stability, career-family balance and orientation to service, while male students or, in a broader scope, those with masculine-type personality put more value on management.